2017
DOI: 10.5037/jomr.2017.8103
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Comparison of Biological Effects of Coe-Pak and Reso-Pac Periodontal Dressings

Abstract: ObjectivesThe purpose of the present study was to compare the cytotoxicity of Reso-Pac and Coe-Pak periodontal dressing.Material and MethodsAccording to ISO-10993-12:2012, 1-, 3- and 7-day extracts of the two periodontal dressings were prepared in cell culture medium and exposed to the two cultured cell lines. Cell viability and proliferation at 24 h and 72 h following exposure were evaluated using quantitative MTT assay.ResultsThe results showed a significant (P < 0.05) reduction in the viability of cells exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
3
17
0
Order By: Relevance
“…At all evaluation times, Reso-pac had fewer cytotoxicity effects than Coe-pak. The results of this study were in accordance with Kadkhodazadeh's study, 8 that showed a difference in cytotoxicity of Reso-pac and Coe-pak groups in their day one extracts. However, in their results, Reso-pac had no-time.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…At all evaluation times, Reso-pac had fewer cytotoxicity effects than Coe-pak. The results of this study were in accordance with Kadkhodazadeh's study, 8 that showed a difference in cytotoxicity of Reso-pac and Coe-pak groups in their day one extracts. However, in their results, Reso-pac had no-time.…”
Section: Discussionsupporting
confidence: 91%
“…No allergic reactions have been reported until now. 8 The use of periodontal dressings is increasing in routine practice since there is still no agreement regarding their positive effects on wound healing after surgery. 6 Greater patient comfort with dressing usage seems to be an important factor in favor of their application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of its self‐attachment to surfaces, flexibility, and softness, BC can also be a good candidate in other dental medicine applications, such as temporal implant in dental extraction alveoli or wound dressing after mucosal implantation . However, although the recognized improved epithelialization and decreased inflammatory reactions during the use of BC‐based periodontal dressing materials, the number of studies of its application in this area is scarce.…”
Section: Applicationsmentioning
confidence: 99%
“…The surgical wound was covered by Coe-pak © and left in place about a week to facilitate quick healing [ Figure 1a – d ]. [ 1 ] Amoxicillin was prescribed as a prophylactic drug to all the patients for 5 days in addition to nonsteroidal anti-inflammatory drugs and instructed to use chlorhexidine 0.2% twice daily as an antiplaque agent for 4 weeks. [ 2 ],[ 3 ] The excised tissues were sent in 10% formalin-containing bulb to the department of oral and maxillofacial pathology for histopathology.…”
Section: Case Reportmentioning
confidence: 99%